Analisis Perkembangan Kredit Bermasalah Terhadap Tingkat Kesehatan Bank (Studi Kasus Pada PT Bank Mandiri Persero TBK) - Praisa Fiftania; Nana Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The background of this research is that the provision of credit by banks must pay attention to the principles of healthy lending. With a case study at PT Bank Mandiri (Persero) Tbk. The purpose of this study was to find out what factors cause non-performing loans, analyze the rate of credit growth, and the level of credit health at PT Bank Mandiri (Persero) Tbk for the 2019-2020 period. This study uses a qualitative descriptive method using NPL financial ratio analysis in calculating non-performing loans through the bank's balance sheet. Bank Indonesia classifies non-productive loans into three categories, namely the Substandard, Doubtful and Loss Category. The results of this study show that the Bank's NPL in 2020 has increased to 3.26% when compared to 2019 of 2.39%. This increase shows that PT Bank Mandiri (Persero) Tbk is facing the COVID-19 pandemic that has been going on since early 2020.